Fullerene‐like Re‐Doped MoS2 Nanoparticles as an Intercalation Host with Fast Kinetics for Sodium Ion Batteries. Issue 5 (20th February 2015) - Woo, Seung Hee; Yadgarov, Lena; Rosentsveig, Rita; Park, Yuwon; Song, Daesun; Tenne, Reshef; Hong, Sung You
Abstract Sodium ion batteries (SIBs) are considered as a promising alternative to threaten the reign of lithium ion batteries (LIBs) among various next‐generation rechargeable energy storage systems, including magnesium ion, metalair, and metalsulfur batteries. Since both sodium and lithium are located in Group 1 of the periodic table, they share similar (electro)chemical properties with regard to ionization pattern, electronegativity, and electronic configuration; thus the vast number of compounds developed from LIBs can provide guidance to design electrode materials for SIBs. However, the larger ionic radius of the sodium cation and unique (de)sodiation processes may also lead to uncertainties in terms of thermodynamic or kinetic properties. Herein, we present the first construction of SIBs based on inorganic fullerene‐like (IF) MoS2 nanoparticles. Closed‐shell‐type structures, represented by C60 fullerene, have largely been neglected for studies of alkali‐metal hosting materials due to their inaccessibility for intercalating ions into the inner spaces. However, IF‐MoS2, with faceted surfaces, can diffuse sodium ions through the defective channels, thereby allowing reversible sodium ion intercalation/deintercalation. Interestingly, Re‐doped MoS2 showed good electrochemical performances with fast kinetics (ca. 74 mA h g−1 at 20 C). N‐type doping caused by Re substitution of Mo in IF‐MoS2 revealed enhanced electrical conductivity and an increased number of diffusion defect sites. Thus, chemical modification of fullerene‐like structures through doping is proven to be a promising synthetic strategy to prepare improved electrodes.